MEDIASI AKSESIBILITAS MODAL UTANG PADA PENGARUH KINERJA LINGKUNGAN TERHADAP FINANCIAL DISTRESS - Puspita Sari; Dian Agustia; Isnalita Isnalita; Mienati Somnya Lasmana (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2023)
This study proves empirically that the accessibility of debt capital mediates the effect of environmental performance on financial distress. This study uses simple mediation analysis to analyze the data and SPSS 24 software to process the data. This study used a purposive sampling method with a total sample of 219 companies in the basic industrial and chemical, mining and agricultural sectors which were listed on the Indonesia Stock Exchange and PROPER Indonesia during 2013-2018. Based on the results of empirical tests, this study found that the accessibility of debt capital does not mediate the effect of corporate environmental performance on financial distress. This is because environmental performance is an indicator that is still relatively new to the Indonesian financial market. Thus, creditors as corporate stakeholders have not considered environmental performance as a guarantee for the company's performance in fulfilling its obligations. However, contrary to these results, the company's environmental performance was found to have an effect on financial distress. Where, companies with good environmental performance tend to have adequate capabilities in managing their resources, especially the company's economic resources. Thus, the results of this study have confirmed the resource-based view theory and the trade-off theory.